The Effect Of Job Satisfaction And Organizational Culture On Employee Performance In The Ceramic Industry Of PT. XYZ Karawang - Rahma, Khansa Nadya Atika; Saputra, Bobby Wiryawan (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
The purpose of the study was to determine the effect of job satisfaction and organizational culture on employee performance in the ceramic industry of XYZ Karawang company. This study was conducted using a quantitative method with SPSS data processing tools. In the study, the researcher used data from the HR division as a reference for the number of target populations, namely employees working in the Wall Ceramic Industry of PT. XYZ in Karawang. The number of samples to be used in this study is 148. Based on the results of the study regarding the effect of organizational culture, job satisfaction on employee performance in the ceramic industry of PT. XYZ Karawang, it can be concluded that organizational culture has a significant effect on employee performance. Job Satisfaction has the most dominant effect on employee performance. The results of the job satisfaction test show the most dominant factor in increasing employee performance. Simultaneously, the two independent variables, namely organizational culture and job satisfaction, have a significant effect on employee performance. The results of the F test show that the combination of the two variables is 61.5% of the variation in employee performance. This means that employee performance is not only caused by one factor but rather a combination of integration between the company's value system (organizational culture) and employee psychological well-being (job satisfaction).